New understanding of primary health care nurse practitioner role optimisation: the dynamic relationship between the context and work meaning - Nancy Côté; Andrew Freeman; Emmanuelle Jean; Jean-Louis Denis (BMC, 2019)
Abstract Background Optimising health professionals' contribution is an essential step in effective and efficient health human resources utilisation. However, despite the considerable efforts made to implement advanced practice nursing roles, including those in primary care settings (PHCNP), the optimisation of these roles remains variable. In this investigation, we report on the subjective work experience of a group of PHCNPs in the province of Quebec (Canada). Methods We used Giddens' structuration theory to guide our study given its' facilitation of the understanding of the dynamic between structural constraints and actors' actions. Using a qualitative descriptive study design, and specifically both individual and focus group interviews, we conducted our investigation within three health care regions in Quebec during 2016-2017. Results Forty-one PHCNPs participated. Their descriptions of their experience fell into two general categories. The first of these, their perception of others' inadequate understanding and valuing of their role, included the influence of certain work conditions, perceived restrictions on professional autonomy and the feeling of being caught between two professional paradigms. The second category, the PHCNPs' sense of engagement in their work, included perspectives associated with the specific conditions in which their work is situated, for example, the fragility of the role depending on the particular clinic/s in which they work or on the individuals with whom they work. This fragility was also linked with certain health care reforms that had been implemented in Quebec (e.g., legislation requiring greater physician productivity). Conclusion Several new insights emerged, for example, the sense of role fragility being experienced by PHCNPs. The findings suggest an overarching link between the work context, the meaning attributed by PHCNPs to their work and their engagement. The optimisation of their role at the patient care level appears to be influenced by elements at the organisational and health system context levels. It appears that role optimisation must include the establishment of work environments and congruent health context structures that favour the implementation and deployment of new professional roles, work engagement, effective collaboration in interprofessional teams, and opportunities to exercise agency. Further research is necessary to evaluate initiatives that endeavour to achieve these objectives.